Developing a Validity Argument Through Abductive Reasoning with an Empirical Demonstration of the Latent Class Analysis. Issue 1 (2nd January 2016) - Wu, Amery D.; Stone, Jake E.; Liu, Yan
Abstract : This article proposes and demonstrates a methodology for test score validation through abductive reasoning. It describes how abductive reasoning can be utilized in support of the claims made about test score validity. This methodology is demonstrated with a real data example of the Canadian English Language Proficiency Index Program (CELPIP)-General test—a program assessing functional English language ability in the community and workplace. Abductive reasoning seeks the enabling conditions through which a claim about a person's ability makes sense. For example, it makes sense that a person has strong functional language proficiency if he or she has been regularly using English to write emails and meet with colleagues at work. A valid test score should be affected by the extent of a person's engagement with such enabling conditions. Empirical evidence that warrants such an abductively reasoned claim is illustrated through a latent class analysis within a structural equation model. Evidence is examined to investigate whether certain classes of test takers who have been differentially engaging in the enabling conditions do, in fact, predict a person's CELPIP-General performance. The steps of the methodology are summarized in the closing section.